2013
DOI: 10.1186/1752-0509-7-141
|View full text |Cite
|
Sign up to set email alerts
|

Systems biology approach to stage-wise characterization of epigenetic genes in lung adenocarcinoma

Abstract: BackgroundEpigenetics refers to the reversible functional modifications of the genome that do not correlate to changes in the DNA sequence. The aim of this study is to understand DNA methylation patterns across different stages of lung adenocarcinoma (LUAD).ResultsOur study identified 72, 93 and 170 significant DNA methylated genes in Stages I, II and III respectively. A set of common 34 significant DNA methylated genes located in the promoter section of the true CpG islands were found across stages, and these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
40
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(42 citation statements)
references
References 126 publications
2
40
0
Order By: Relevance
“…We observed a few genes of homeobox family in our signature. LBX1 or ladybird homeobox 1 gene has been reported to be hyper methylated in prostate and lung cancer 35,36 and is known to play a role in epithelialmesenchymal transition by regulating genes like ZEB1, ZEB2, and TGFB2. 37 EVX1 or even skipped homeobox-1 hyper methylation is also associated with prostate and lung cancer progression while a recent report by Mallak et al demonstrated reduced expression of EVX1 to be associated with ESCC aggressiveness by being a target gene in BMP signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…We observed a few genes of homeobox family in our signature. LBX1 or ladybird homeobox 1 gene has been reported to be hyper methylated in prostate and lung cancer 35,36 and is known to play a role in epithelialmesenchymal transition by regulating genes like ZEB1, ZEB2, and TGFB2. 37 EVX1 or even skipped homeobox-1 hyper methylation is also associated with prostate and lung cancer progression while a recent report by Mallak et al demonstrated reduced expression of EVX1 to be associated with ESCC aggressiveness by being a target gene in BMP signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…A systems biology approach was utilized for a stage-wise characterization of epigenetic genes and epigenetic subnetwork analysis identified a set of seven conserved genes across all stages of lung adenocarcinoma (90). The methylation status of HOXD3, ARHGDIB, AGAP2 genes was reported to be involved in cell signaling and cytoskeletal organization in squamous cell lung carcinoma.…”
Section: Epigenomicsmentioning
confidence: 99%
“…It's a transcription factor with known positive and negative regulatory activities in development and differentiation [84] and seemed to be a tumor suppressor [85] . NKX6.2 is respectively detected in a variety of different neoplasms, like brain tumor [86] , bladder cancer [87] , renal cell carcinoma [88][89] , and lung adenocarcinoma [90] . By so far, no NKX6.2 expression is reported in gastrointestinal neoplasms.…”
Section: Nkx62mentioning
confidence: 99%